Interfaces entre comportamento sexual de risco e uso de cocaína e álcool em uma amostra de pacientes em tratamento para uso de substâncias - Dallelucci, Claudia Chaves [UNIFESP] (2018)
Objective: To study risky sexual behavior, primarily inconsistent condom use and the presence of multiple partners in alcohol and cocaine users. We also research the association of risky sexual behavior with other variables, such as schooling and psychiatric comorbidities. Methodology: Observational study of a clinical sample of initial interviews of patients seeking treatment in an outpatient addiction unit. The variables were organized into four blocks: sociodemographic, substance use, sexual behavior and psychiatric symptoms. For risky sexual behavior was considered the inconsistent use of condoms and the presence of multiple sexual partners in the last six months. An exploratory analysis of the association between the variable "risky sexual behavior" and the other variables was performed using Pearson's chisquare (X2), followed by a multivariate logistic regression analysis, with a significance level of 5% for all tests. Results: 95.9% of the sample are men and 4.1% are women, with a mean age of 37 years. After analyzing the variables with the presence or absence of risky sexual behavior, data presentig statical significance of association with the presence of risky sexual behavior were included in the logistic regression, being age, schooling, work activity, cocaine use concomitantly alcohol, having sex under substance influence in the last six months, and a history of childhood sexual abuse. Corroborating some data in the literature, women seek less treatment for dependence than men, considering the disparity of the sample in an outpatient treatment unit. Age was an independent risk factor for risky sexual behavior, even in the adult population. Other structural factors, such as schooling and the presence of formal employment, have tended to influence as much as the use of substances in risky sexual behaviors. Conclusion: The risk of the psychoactive users population of contracting sexually transmitted infecctions is high. However, attributing this risk only to the substance use is a simplistic and difficult route to be proven. Other structural factors such as age, schooling and history of abuse can influence decision making for safe sex.